2017
DOI: 10.36076/ppj.2017.184
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Ketamine Administration for Thoracotomy Pain

Abstract: Background: Of all the postsurgical pain conditions, thoracotomy pain poses a particular therapeutic challenge in terms of its prevalence, severity, and ensuing postoperative morbidity. Multiple pain generators contribute to the severity of post-thoracotomy pain, and therefore a multimodal analgesic therapy is considered to be a necessary strategy. Along with opioids, thoracic epidural analgesia, and paravertebral blocks, N-Methyl-D-Aspartate (NMDA) receptor antagonists such as ketamine have been used as adjuv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 25 publications
2
4
0
Order By: Relevance
“…Ketamine has been evaluated in three recent reviews for orthopedic surgery, 42,43 and thoracotomy. 44 Consistent with the current review, the majority (two of three) indicated results to be inconclusive. 43,44 In disagreement, one narrative systematic review evaluating various interventions for adults receiving primary total knee arthroplasty concluded a treatment effect of ketamine claiming “good-quality evidence for a small benefit” 42 ; however, their conclusion was based on one small randomized controlled trial.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…Ketamine has been evaluated in three recent reviews for orthopedic surgery, 42,43 and thoracotomy. 44 Consistent with the current review, the majority (two of three) indicated results to be inconclusive. 43,44 In disagreement, one narrative systematic review evaluating various interventions for adults receiving primary total knee arthroplasty concluded a treatment effect of ketamine claiming “good-quality evidence for a small benefit” 42 ; however, their conclusion was based on one small randomized controlled trial.…”
Section: Resultssupporting
confidence: 79%
“…19,25 Ketamine has been evaluated in three recent reviews for orthopedic surgery, 42,43 and thoracotomy. 44 Consistent with the current review, the majority (two of three) indicated results to be inconclusive. 43,44 In disagreement, one narrative systematic review evaluating various interventions for adults receiving primary total knee arthroplasty concluded Copyright © 2021, the American Society of Anesthesiologists.…”
Section: Ketaminesupporting
confidence: 79%
“…Moreover, we also used esketamine in epidural analgesia to increase the effect of local anesthesia. [30][31][32] Considering that NMDA receptor antagonists have been suggested to prevent central sensitization from surgical wounds, we presume that esketamine may have a similar effect. Despite the advantage of NMDA receptor activation, the neurotoxicity of esketamine, including delusion and dizziness, was not observed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies showed that ketamine alleviates acute pain for patients receiving thoracic surgery and a few studies showed no benefits. Furthermore, studies did not show evidence that ketamine might provide precaution in PTPS (28)(29)(30)(31)(32). In this background, we aim to explore the analgesic effect of intravenous esketamine for acute and chronic pain in VATS patients.…”
Section: Ethics Statementmentioning
confidence: 99%